A comparative proteomic analysis of bile for biomarkers of cholangiocarcinoma. Issue 6 (May 2017) - Laohaviroj, Marut; Potriquet, Jeremy; Jia, Xinying; Suttiprapa, Sutas; Chamgramol, Yaovalux; Pairojkul, Chawalit; Sithithaworn, Paiboon; Mulvenna, Jason; Sripa, Banchob
Cholangiocarcinoma is a primary malignant tumor of the bile duct epithelium. Cholangiocarcinoma is usually detected at an advanced stage when successful treatment is no longer possible. As the tumor originates from the bile duct epithelium, bile is an ideal source of tumor biomarkers for cholangiocarcinoma. In this study, we used a quantitative proteomics approach to identify potential tumor-associated proteins in the bile fluid of six cholangiocarcinoma patients. Three different gross-appearance tumor types were used in the analysis: mass-forming type ( n  = 2), periductal infiltrating type ( n  = 2), and intraductal growth type ( n  = 2). Two bile samples from non-cancerous patients were used as controls. Isobaric labeling, coupled with Tandem mass spectrometry, was used to quantify protein levels in the bile of cholangiocarcinoma and control patients. In all, 63 proteins were significantly increased in cholangiocarcinoma bile compared to normal bile. Alpha-1-antitrypsin was one of the overexpressed proteins that increased in cholangiocarcinoma bile samples. Immunohistochemical analysis revealed that alpha-1-antitrypsin was detected in 177 (50%) of 354 cholangiocarcinoma tissues from our Tissue Bank. Immunoblotting of 54 cholangiocarcinoma bile samples showed that alpha-1-antitrypsin was positive in 38 (70%) samples. Fecal enzyme-linked immunosorbent assay showed that alpha-1-antitrypsin level was able to distinguish cholangiocarcinoma patients from normal individuals. In conclusion, alpha-1-antitrypsin is a potential marker for early diagnosis of cholangiocarcinoma.